Better 21C credentials : evaluating the promise, perils and disruptive potential of digital credentials. - Oliver, Beverley (Office for Learning and Teaching, 2016)
Resource produced from a project that proposed to connect Australian higher education providers with national and international networks of innovators and scholars in emerging practices in digital curation and credentialling - that is, conferring macro and micro credentials based on evidence of learning richer than codified marks, grades and credits. The paper analyses 19 case studies.